Annealing effect on the structural and optical properties of embedded au nanoparticles in silicon suboxide films - Chan, K.; Goh, B.T.; Rahman, S.A.; Muhamad, M.R.; Dee, C.F.; Aspanut, Z. (2012)
Au/SiO x nanocomposite films have been fabricated by co-sputtering Au wires and SiO 2 target using an RF magnetron co-sputtering system before the thermal annealing process at different temperatures. The structural and optical properties of the samples were characterized using X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), optical transmission, and reflection spectroscopy. XPS analysis confirms that the as-prepared SiO x films are silicon-rich suboxide films. FESEM images reveal that with an increase in annealing temperature, the embedded Au NPs tend to diffuse toward the surface of the SiO x films. In IR spectra, the intensity of the Si-O-Si absorption band increases with the annealing temperature. Optical spectra reveal that the position and intensity of the surface plasmon resonance (SPR) peak are dominated by the effect of the inter-particle distance and size of the Au NPs embedded in the SiO x films, respectively. The SPR absorption peak shows the blue-shift from 672 to 600 nm with an increase in annealing temperature. The growth of silica nanowires (SiO x NWs) is observed in the film prepared on a c-Si substrate instead of a quartz substrate and annealed at temperatures of 1000 Â°C. Â© 2012 Elsevier Ltd. All rights reserved.